Are prisons obsolete? - Davis, Angela Y. (Angela Yvonne), 1944- (Open Media book., 2003)
Amid rising public concern about the proliferation and privatization of prisons, and their promise of enormous profits, world-renowned author and activist Angela Y. Davis argues for the abolition of the prison system as the dominant way of responding to America's social ills. "In thinking about the possible obsolescence of the prison," Davis writes, "we should ask how it is that so many people could end up in prison without major debates regarding the efficacy of incarceration." Whereas Reagan-era politicians with "tough on crime" stances argued that imprisonment and longer sentences would keep communities free of crime, history has shown that the practice of mass incarceration during that period has had little or no effect on official crime rates: in fact, larger prison populations led not to safer communities but to even larger prison populations. As we make our way into the twenty-first century-two hundred years after the invention of the penitentiary-the question of prison abolition has acquired an unprecedented urgency. Backed by growing numbers of prisons and prisoners, Davis analyzes these institutions in the U.S., arguing that the very future of democracy depends on our ability to develop radical theories and practices that make it possible to plan and fight for a world beyond the prison industrial complex.